Polyvinyl alcohol film and preparation method thereof

By preparing the polyvinyl alcohol film under specific conditions, the problem of insufficient durability of the polyvinyl alcohol polarizing film in high temperature and high temperature and high humidity environments is solved, and the effect of improving the durability and optical performance of the polarizing film is achieved.

CN119019799BActive Publication Date: 2025-02-07ANHUI WANWEI UPDATED HIGH TECH MATERIAL CO LTD +1

Patent Information

Application Number
CN202411507815.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing polyvinyl alcohol polarizing films have insufficient durability in high temperature and high temperature and high humidity environments, which affects the imaging performance of the display panel.

Method used

By preparing a polyvinyl alcohol film, the saturated water absorption amount of its amorphous structure is x, the increased water absorption amount of crystal surface defect structure failure is y, which meets x/(x+y) from 0.82 to 0.93, and the softening point is 65℃ To 75°C, the swelling is 180% to 220%.

Benefits of technology

The durability of the polyvinyl alcohol polarizing film is improved and the optical performance in high temperature and high temperature and high humidity environments are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The present invention relates to the technical field of polyvinyl alcohol, and in particular to a polyvinyl alcohol film and a preparation method thereof. The saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x, and the water absorption increased by the crystal surface defect structure destruction in the polyvinyl alcohol film is y, and x / (x+y) is 0.82 to 0.93; the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%. Under the above conditions, the durability of the polyvinyl alcohol polarizing film prepared by using the polyvinyl alcohol film is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyvinyl alcohol films, and in particular to a polyvinyl alcohol film and a preparation method thereof. Background Art

[0002] Polyvinyl alcohol (PVA) film is mainly used to prepare polarizing film, and its end products are used in various types of liquid crystal displays, such as display panels for televisions, computer monitors, mobile phones, car navigation and wearable electronic devices. The retention rate of the optical properties of PVA polarizing film under high temperature and high temperature and high humidity environment is a key indicator for evaluating the durability of PVA polarizing film. As display panels develop towards thinner, more durable and more transparent directions, especially in automotive applications, higher and higher requirements are placed on the durability of polyvinyl alcohol polarizing film and its upstream optical film. Summary of the invention

[0003] The main object of the present invention is to provide a polyvinyl alcohol film, aiming to improve the durability of the polyvinyl alcohol polarizing film.

[0004] To achieve the above object, the present invention provides a polyvinyl alcohol film, wherein the saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x, the water absorption increased by the crystal surface defect structure destruction in the polyvinyl alcohol film is y, and x / (x+y) is 0.82 to 0.93;

[0005] The softening point of the polyvinyl alcohol film is 65° C. to 75° C., and the swelling degree of the polyvinyl alcohol film is 180% to 220%.

[0006] Optionally, x / (x+y) is 0.84 to 0.89.

[0007] Optionally, the polyvinyl alcohol film has a crystallinity of 35% to 45%, and a melting point of 210°C to 230°C.

[0008] Optionally, the step of testing the saturated water absorption of the amorphous structure in the polyvinyl alcohol film comprises: soaking at least one portion of the polyvinyl alcohol film in deionized water at a preset temperature for a preset time t1, taking out the polyvinyl alcohol film after the amorphous structure in the polyvinyl alcohol film has finished absorbing water, scraping off the water droplets on the surface of the polyvinyl alcohol film and weighing it, which is calculated as m x1 , the polyvinyl alcohol film is dried and weighed, which is m x2 The saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x = (m x1 -m x2 ) / m x2 *100%;

[0009] The testing step of the sum of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film and the water absorption increased due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film comprises: soaking at least one portion of the polyvinyl alcohol film in deionized water at a preset temperature for a preset time t2 to destroy the crystal surface defect structure in the polyvinyl alcohol film, and after the destroyed crystal surface defect structure finishes absorbing water, taking out the polyvinyl alcohol film, scraping off the water droplets on the surface of the polyvinyl alcohol film and weighing it, which is calculated as m x3 , the polyvinyl alcohol film is dried and weighed, which is m x4 The sum of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film and the water absorption increased by the crystal surface defect structure in the polyvinyl alcohol film is x+y= (m x3 -m x4 ) / m x4 *100%.

[0010] Optionally, the preset temperature is 30° C., the t1 is 1 min, and the t2 is 15 min.

[0011] Optionally, the present application also provides a method for preparing a polyvinyl alcohol film, comprising:

[0012] Dissolving polyvinyl alcohol and additives in a solvent to obtain a film casting stock solution;

[0013] The film casting solution is subjected to degassing, tape casting and pre-drying to obtain a pre-dried film;

[0014] The pre-dried film is heat-treated to obtain a polyvinyl alcohol film.

[0015] Optionally, in the step of obtaining a pre-dried film after degassing, casting and pre-drying the film casting solution, the water content of the pre-dried film is 8% to 15%;

[0016] and / or, in the step of heat-treating the pre-dried film to obtain a polyvinyl alcohol film, the water content of the polyvinyl alcohol film is 0.1% to 5%;

[0017] And / or, in the step of obtaining a pre-dried film after degassing, tape casting and pre-drying the film casting stock solution, the water content of the liquid film after tape casting is 15% to 35%.

[0018] Optionally, the water content of the polyvinyl alcohol film is 0.5% to 3.5%;

[0019] And / or, the water content of the liquid film after tape casting is 18% to 30%.

[0020] Optionally, the step of heat-treating the pre-dried film to obtain a polyvinyl alcohol film includes: heat-treating the pre-dried film in sequence using n temperature stages to obtain a polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first increasing and then decreasing, and 2≤n≤20.

[0021] Optionally, the step of heat-treating the pre-dried film in sequence using n temperature stages to obtain a polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first increasing and then decreasing, comprises:

[0022] The pre-dried film is heat-treated for a time of t, and the pre-dried film is heat-treated at a first temperature range of 50° C. to 80° C. under a condition of 0% t to 20% t;

[0023] Under the condition of 20%t to 40%t, the pre-dried film is heat-treated with a second temperature, wherein the second temperature is 55°C to 95°C;

[0024] Under the condition of 40%t to 60%t, the pre-dried film is heat-treated at a third temperature, wherein the third temperature is 70°C to 100°C;

[0025] Under the condition of 60%t to 80%t, the pre-dried film is heat-treated at a fourth temperature, wherein the fourth temperature is 100°C to 130°C;

[0026] The pre-dried film is heat treated at a fifth temperature under a condition of 80%t to 100%t, wherein the fifth temperature is 50°C to 98°C; and a polyvinyl alcohol film is obtained.

[0027] Optionally, in the step of sequentially heat-treating the pre-dried film at n temperature stages, the step includes drying the pre-dried film with a fan;

[0028] The wind speed of the fan in the first temperature section is 5.9m / s to 12.4m / s, the wind speed of the fan in the second temperature section is 6.6m / s to 13.1m / s, the wind speed of the fan in the third temperature section is 13.2m / s to 19.7m / s, the wind speed of the fan in the fourth temperature section is 10.5m / s to 17.0m / s, and the wind speed of the fan in the fifth temperature section is 11.5m / s to 18.0m / s.

[0029] Optionally, the wind speed of the fan in the first temperature section is 8.1m / s to 10.3m / s, the wind speed of the fan in the second temperature section is 8.8m / s to 10.9m / s, the wind speed of the fan in the third temperature section is 15.4m / s to 17.5m / s, the wind speed of the fan in the fourth temperature section is 12.7m / s to 14.9m / s, and the wind speed of the fan in the fifth temperature section is 13.7m / s to 15.8m / s.

[0030] The polyvinyl alcohol film provided by the present application has a saturated water absorption of an amorphous structure in the polyvinyl alcohol film of x, an increased water absorption due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film of y, and x / (x+y) is 0.82 to 0.93, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%. x is the saturated water absorption of an amorphous structure in the polyvinyl alcohol film, y is the increased water absorption due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film, x / (x+y) is 0.82 to 0.93, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%. Under the above conditions, the durability of the polyvinyl alcohol polarizing film prepared using the polyvinyl alcohol film is improved. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0033] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0035] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0036] One of the factors affecting the durability of the polarizing film includes the stability of the PVA-iodine complex in the polarizing film. The stability of the PVA-iodine complex is further affected by the structure of the PVA film. The specific surface area, stability and crystal content of the crystals in the PVA film determine the content and stability of the fibrous PVA-polyiodide ion composite structure formed during the processing of the polarizing film. The polyvinyl alcohol film that meets the following conditions of this application has a crystal network with a high crystal specific surface area, sufficient crystal content and appropriate crystal stability, which is conducive to obtaining a polarizing film with excellent durability.

[0037] The specific conditions are: x / (x+y) is 0.82 to 0.93, x is the saturated water absorption of the amorphous structure in the polyvinyl alcohol film, y is the increased water absorption in the polyvinyl alcohol film due to the destruction of the crystal surface defect structure, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%.

[0038] Specifically, during the processing of PVA polarizing film, the PVA optical film is dyed and stretched to form dichroic dye molecules mainly composed of iodine trianions and iodine pentaanions arranged along the orientation direction of the PVA chain, which is a key structure affecting the optical properties of the polarizing film. During the use of the polarizing film, under the action of long-term high temperature or high temperature and high humidity conditions, the complexed polyiodide ions will undergo changes such as decomplexation, decomposition or oxidation, and diffuse out of the system in the form of iodine element, causing the ratio of iodine trianions to iodine pentaanions inside the polarizing film to change. Macroscopically, it gradually manifests as the polarizing film transmitting red light, transmitting blue light, and the overall color becoming lighter and unable to display. The imaging performance of the display panel is seriously affected, and even a white screen phenomenon occurs. Therefore, how to improve the stability of polyiodide ions (PVA-iodine trianions, PVA-iodine pentaanions) in the polarizing film is the key to improving the durability of the polarizing film, especially the automotive polarizing film.

[0039] At present, the solution to improve the durability of PVA polarizing film is mainly to adjust the protective film composition, adhesive process, dyeing process and boric acid cross-linking agent during the polarizing film processing. Although the above solutions can solve the problem of poor durability to a certain extent, they inevitably introduce other problems, such as reduced transmittance of polarizing film, decreased mechanical properties, increased thickness, production line difficulties, large-scale equipment transformation, and significantly increased costs. It is difficult to obtain PVA polarizing film with excellent performance in all aspects.

[0040] The structural factors that determine the durability of the polarizing film in this application include the stability of the PVA-iodine complex, which is determined to a certain extent by the chemical composition and microstructure of the upstream material PVA optical film, where the larger the specific surface area of ​​the crystal, the more amorphous regions around the crystal, and the more stable the PVA-iodine trianion and PVA-iodine pentanion formed. The process adjustment of the polarizing film processing can only achieve a partial improvement effect, while the durability optimization of the upstream PVA optical film material has the advantages of more significant effect and less impact on the process, equipment, and product performance of the downstream polarizing film processing.

[0041] The present application proposes a polyvinyl alcohol film, in which the saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x, the increased water absorption in the polyvinyl alcohol film due to the destruction of the crystal surface defect structure is y, and x / (x+y) is 0.82 to 0.93, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%.

[0042] The amorphous region of a polymer material refers to the area where the polymer chain segments are not arranged in regular parallel order.

[0043] The polymer crystal structure refers to the structure formed by regular parallel arrangement of molecular chain segments.

[0044] Crystal defects in polymers refer to crystalline regions where the molecular chain segments are irregularly arranged and have poor stability, usually at the junction of the crystal and amorphous regions, that is, the crystal surface.

[0045] x is the saturated water absorption of the amorphous structure in the polyvinyl alcohol film, y is the increased water absorption in the polyvinyl alcohol film due to the destruction of the crystal surface defect structure, x / (x+y) is 0.82 to 0.93, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%. Under the above conditions, the durability of the polyvinyl alcohol polarizing film prepared using the polyvinyl alcohol film is improved.

[0046] It is understandable that polyvinyl alcohol is a semi-crystalline polymer, which is composed of a crystalline structure and an amorphous structure. The crystal exists between the amorphous regions in the form of physical cross-linking points, and together with the amorphous structure, it forms a crystalline cross-linking network. The saturated water absorption x of the amorphous structure in the polyvinyl alcohol film is related to the content of the amorphous structure. The water absorption y increased by the destruction of the crystal surface defect structure in the polyvinyl alcohol film is related to the content, stability and specific surface area of ​​the crystal structure. It is understandable that because there are defects on the surface of the crystal, under the action of a certain temperature and water, the crystal surface defect structure gradually dissolves and becomes an amorphous region. The increase in the water absorption y due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film is related to the content, stability and specific surface area of ​​the crystal structure. The water absorption refers to the increased water absorption when the part of the structure becomes amorphous; the experiment found that the polarizing film prepared by the polyvinyl alcohol film that meets the above conditions (x / (x+y) is 0.82 to 0.93), and the softening point and swelling degree of the polyvinyl alcohol film meet the above ranges, has good durability. It can be understood that the specific surface area, stability and crystal content of the crystals in the polyvinyl alcohol film determine the content and stability of the fibrous PVA-polyiodide ion composite structure formed in the processing of the polarizing film. A crystal network with high crystal specific surface area, sufficient crystal content and suitable crystal stability is conducive to obtaining a polarizing film with excellent durability.

[0047] It is understandable that when the polyvinyl alcohol film absorbs water and swells in water, the amorphous structure absorbs water and swells first, which is a relatively fast process. Then, water molecules gradually destroy the hydrogen bonds of the defective structure on the surface of the polyvinyl alcohol crystal, destroying the less stable defective structure until a stable crystal is encountered. This process is relatively slow, and the less stable defective structure is equivalent to being wrapped outside the stable crystal. Therefore, the more unstable defective structures account for, the larger the specific surface area of ​​the crystal particles and the smaller the size of a single crystal. At the same time, the softening point and swelling degree of the polyvinyl alcohol film meet the above ranges. The polyvinyl alcohol film that meets the above conditions has an appropriate amount of crystal content and stability, and a large crystal specific surface area.

[0048] It can be understood that the softening point and swelling degree of the polyvinyl alcohol film meet the above ranges, and the polyvinyl alcohol film has a high crystal specific surface area (small and numerous crystals), sufficient crystal content, and a stable crystal network, which is beneficial to improving the dyeing efficiency, dyeing color and durability when preparing the polarizing film, and reducing the risk of film breakage when stretching the polarizing film.

[0049] It can be understood that if the softening point of the polyvinyl alcohol film is too high and the swelling degree is too low, there is a greater possibility that its crystallinity is too high, which will lead to reduced dyeing efficiency, poor dyeing chromaticity and durability during the preparation of the polarizing film; if the softening point is too low and the swelling degree is too high, there is a greater possibility that its crystallinity is too low, which will cause an increase in the dissolution of polyvinyl alcohol during the preparation of the polarizing film, and a decrease in the elongation at break, which will easily cause the film to break during stretching.

[0050] In the above 0.82 to 0.93, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.90, 0.91, 0.92, 0.93, etc., and the range values ​​between any two of the above point values.

[0051] In one embodiment, when x / (x+y) is 0.84 to 0.89, the durability of the polyvinyl alcohol polarizing film prepared using the polyvinyl alcohol film is better.

[0052] In the above 0.84 to 0.89, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, etc., as well as the range values ​​between any two of the above point values.

[0053] In one embodiment, the crystallinity of the polyvinyl alcohol film is 35% to 45%, and the melting point of the polyvinyl alcohol film is 210° C. to 230° C.

[0054] Crystallinity is an important parameter to measure the proportion of the crystalline part in a material.

[0055] The melting point of a crystal refers to the temperature at which the polymer crystal melts at the fastest melting rate when heated at a certain heating rate. The melting point of a material can be tested by differential scanning calorimetry (DSC). DSC is a thermal analysis technique that measures the heat difference between a sample and a reference under a precisely controlled temperature program. During the heating process, when the sample melts, it absorbs heat and an endothermic peak appears. By analyzing the peak shape characteristics of these peaks, information such as the melting point and melting enthalpy can be obtained.

[0056] The moisture content of the polyvinyl alcohol film is measured using a Mettler-Toledo HE-53 halogen lamp rapid moisture meter, or other equipment with the same principle, at 120°C for 40 minutes.

[0057] DSC melting point and crystallinity, using a differential scanning calorimeter, the sample is heated from 40°C to 240°C at a heating rate of 10°C. The endothermic peak that appears is the melting peak of the polyvinyl alcohol crystal. The melting point is determined and the integrated enthalpy value is calculated. The enthalpy value ΔHc of 100% crystalline PVA is 138.6 J / g, and the crystallinity calculation formula is as follows:

[0058] .

[0059] The softening point refers to the temperature at which polyvinyl alcohol begins to soften and become fluid during heating. The softening point test can refer to the American Society for Testing and Materials standard ASTM D36-95 "Determination of the softening point of asphalt" to perform the softening point test of polyvinyl alcohol film.

[0060] Fix the polyvinyl alcohol film in a copper ring of specified shape and size, place a steel ball with a mass of 3.5g in the center of the copper ring, immerse it in deionized water, and increase the temperature at a rate of 5℃ / min until the polyvinyl alcohol film softens and sags, and the sag distance of the steel ball exceeds 25mm. Record the water temperature at this time.

[0061] The softening point can measure the size, perfection and content of the crystal. A high softening point generally indicates a larger crystal size, a more perfect crystal structure and a higher content; a low softening point generally indicates a smaller crystal size, a more defective crystal structure and a lower content.

[0062] Swelling degree refers to the parameter of the material's characteristic of absorbing liquid and expanding in liquid. The test method of swelling degree is: cut a 10*200mm film sample, swell in 500mL of 30℃ water for 30 minutes, centrifuge for 5min at 3000rpm, and weigh it as m10. Dry it in a 120℃ blast oven for 2h, take it out and weigh it as m20, swelling degree = m10 / m20 *100%; swelling degree usually represents the amorphous region content of polyvinyl alcohol, the greater the swelling degree, the more amorphous region, and the lower the crystallinity; the smaller the swelling degree, the less amorphous region, and the higher the crystallinity.

[0063] It is understandable that the crystallinity and melting point of the polyvinyl alcohol film satisfy the above ranges, which is conducive to obtaining a crystal cross-linked network with high crystal specific surface area, suitable crystal stability and sufficient crystal content, thereby reducing the risk of film breakage during stretching of the polarizing film.

[0064] In the above 35% to 45%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, etc., and the range values ​​between any two of the above point values.

[0065] In the above-mentioned 210℃ to 230℃, the values ​​include the minimum and maximum values ​​of the range, and every value between such minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 210℃, 211℃, 212℃, 213℃, 214℃, 215℃, 217℃, 219℃, 220℃, 221℃, 224℃, 225℃, 227℃, 228℃, 229℃, 230℃, etc., and the range values ​​between any two of the above-mentioned point values.

[0066] In the above-mentioned 65℃ to 75℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 65℃, 66℃, 67℃, 68℃, 69℃, 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0067] In the above 180% to 220%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 180%, 181%, 183%, 184%, 187%, 189%, 190%, 191%, 192%, 194%, 196%, 199%, 200%, 201%, 205%, 210%, 211%, 215%, 218%, 220%, etc., and the range values ​​between any two of the above point values.

[0068] In one embodiment, during the test of x / (x+y), the following steps may be used. Specifically, at least two polyvinyl alcohol films to be tested are prepared, at least one is used to test to obtain the x value, and at least another is used to test to obtain the x+y value.

[0069] The step of obtaining the x value comprises: soaking at least one of the polyvinyl alcohol films in deionized water at a preset temperature for a preset time t1, taking out the polyvinyl alcohol film after the amorphous structure in the polyvinyl alcohol film has finished absorbing water, scraping off the water droplets on the surface of the polyvinyl alcohol film, and weighing it, which is calculated as m x1 , the polyvinyl alcohol film is dried and weighed, which is m x2 , the saturated water absorption of the amorphous structure in the polyvinyl alcohol film x = (m x1 -m x2 ) / m x2 *100%.

[0070] The step of obtaining the x+y value comprises: soaking at least one of the other polyvinyl alcohol films in deionized water at a preset temperature for a preset time t2, so that the crystal surface defect structure in the polyvinyl alcohol film is destroyed, and after the crystal surface defect structure to be destroyed has finished absorbing water, the polyvinyl alcohol film is taken out, and the water droplets on the surface of the polyvinyl alcohol film are scraped off and weighed, which is calculated as m x3 , the polyvinyl alcohol film is dried and weighed, which is m x4 The sum of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film and the increased water absorption due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film is x+y= (m x3 -m x4 ) / m x4 *100%.

[0071] In the above test process, the preset temperature can be 15°C to 45°C, t1 and t2 can be 0.1min to 30min, and the thickness of the polyvinyl alcohol film to be tested can be 30um to 60um. It can be understood that as the temperature increases, the water absorption rate of the polyvinyl alcohol film will increase and the water absorption time will shorten. In the process of testing the water absorption ratio, the water absorption time is controlled according to the actual test conditions.

[0072] In one embodiment, the preset temperature is 30° C., t1 is 1 min, and t2 is 15 min.

[0073] It is understandable that the water absorption rate of the polyvinyl alcohol film at different temperatures is different. Theoretically, the higher the temperature, the higher the water absorption rate will be. In the present application, the water absorption of the polyvinyl alcohol film at 30°C in 1 minute can be used as the water absorption of the amorphous structure, and the water absorption in 15 minutes can be used as the water absorption of the amorphous structure in the polyvinyl alcohol film and the water absorption increased due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film. That is, it can be considered that the ratio of the water absorption of the polyvinyl alcohol film at 30°C in 1 minute to the water absorption in 15 minutes is 0.82 to 0.93. It can be understood that the durability of the polarizing film is better in the range of 0.84 to 0.89.

[0074] It can be understood that the ratio of the water absorption of the polyvinyl alcohol film in 1 minute and 15 minutes at 30°C can represent the ratio of the fast swelling part (amorphous structure) to the slow swelling part (amorphous structure + increased water absorption due to the destruction of the crystal surface defect structure) in the polyvinyl alcohol film, which respectively correspond to the swelling of the amorphous region and the dissolution process of the crystal surface defect structure. The smaller the ratio, the larger the crystal specific surface area, the smaller the average volume, and the more unstable the crystal; the larger the ratio, the smaller the crystal specific surface area, the larger the average volume, the more stable the crystal, and the higher the polyvinyl alcohol network structure. The size, stability and number of crystal structures will affect the complex stability of hydroxyl groups and iodide ions in the polyvinyl alcohol network structure. The polyvinyl alcohol network structure that meets the above ratio has a large number of small-sized crystal structures, and also has an appropriate amount of crystal structures. The iodine ions are more stably complexed with hydroxyl groups in the above polyvinyl alcohol network structure, making it difficult for iodine to separate from the polyvinyl alcohol network structure. That is, the more stable the polyiodide ions formed by PVA and iodine are, the less likely they are to be destroyed by high temperature and high humidity environments, thereby improving the durability of the polyvinyl alcohol polarizing film prepared using the polyvinyl alcohol film.

[0075] It is understandable that when polyvinyl alcohol swells in water, the amorphous region first absorbs water and expands. For polyvinyl alcohol films with a thickness of 30um to 60um, this process mainly occurs within one minute. Subsequently, water molecules gradually destroy the hydrogen bonds of the surface defect structure of the polyvinyl alcohol crystal, destroying the less stable crystal surface defect structure until a stable crystal is encountered. This process is slow and is currently believed to be basically completed within 15 minutes at 30°C. The less stable crystal surface defect structure is equivalent to being wrapped outside the stable crystal. Therefore, the more unstable crystal surface defect structures account for, the larger the specific surface area of ​​the crystal particles and the smaller the size of a single crystal.

[0076] It is understandable that the crystalline state of polymer films is mainly analyzed by DSC (Differential Scanning Calorimetry) crystallography and X-ray crystallography in the field of basic research. These analysis methods are costly, difficult, and difficult to process data, and are prone to large errors. This application evaluates the crystallization properties of polyvinyl alcohol films by the absorption and swelling properties of water in the amorphous state of the polyvinyl alcohol film and the defective structure of the crystal surface damage. The crystal state is mainly judged based on the kinetic analysis of the swelling rate. Furthermore, conventional evaluation methods such as softening point and swelling degree are combined to characterize the polymer crystals.

[0077] In the above-mentioned 15℃ to 45℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 15℃, 18℃, 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, etc., and the range values ​​between any two of the above-mentioned point values.

[0078] In the above 0.1min to 30min, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1min, 0.5min, 1min, 5min, 10min, 12min, 16min, 19min, 20min, 22min, 25min, 28min, 30min, etc., and the range values ​​between any two of the above point values.

[0079] In the above-mentioned 30um to 60um, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 30um, 32um, 35um, 38um, 40um, 45um, 50um, 55um, 60um, etc., and the range values ​​between any two of the above-mentioned point values.

[0080] In one embodiment, the present application also provides a method for preparing a polyvinyl alcohol film, comprising: dissolving polyvinyl alcohol and additives in a solvent to obtain a casting solution; degassing, casting and pre-drying the casting solution to obtain a pre-dried film; and heat-treating the pre-dried film to obtain a polyvinyl alcohol film.

[0081] For example, polyvinyl alcohol and additives are dissolved in a solvent to prepare a casting solution, which is then extruded and degassed, cast through a die, pre-dried by a drying roller, dried in a heat treatment oven, and finally rolled up to obtain a polyvinyl alcohol film.

[0082] In one embodiment, in the step of obtaining a pre-dried film after degassing, casting and pre-drying the casting solution, the water content of the liquid film after casting is 15% to 35%. It is understandable that if the water content of the liquid film after casting is too high, it will be difficult to peel off, and the load of the subsequent pre-drying stage will increase; if the water content of the liquid film after casting is too low, the equipment load will be too large and the productivity will decrease.

[0083] In one embodiment, the casting solution is degassed, cast and pre-dried to obtain a pre-dried film, and the water content of the pre-dried film is 8% to 15%. It can be understood that too low a water content is not conducive to the formation of a uniform and dense polyvinyl alcohol crystal network, so that the prepared polyvinyl alcohol polarizing film has a larger crystallinity and a smaller specific surface area, resulting in poor stability of the crystal cross-linking network, which is not conducive to improving durability and tensile properties. For example, if the water content of the pre-dried film is too low, it may cause uneven crystal growth, forming a loose network structure, and affecting the tensile properties of the material.

[0084] Too high a moisture content is not conducive to the subsequent heat treatment process. For example, during the heat treatment of a pre-dried film that is not fully dried, the residual moisture will turn into steam due to heating, which may cause dripping, which will affect the appearance and quality of the product. If a plasticizer (such as glycerol) is added to the pre-dried film, during the heat treatment process, if the moisture content is too high, the plasticizer may migrate to the surface of the material along with the moisture and evaporate, and gradually condense into droplets on the film surface, which will also cause the film appearance and tensile properties to deteriorate.

[0085] In one embodiment, in the step of heat-treating the pre-dried film to obtain the polyvinyl alcohol film, the water content of the polyvinyl alcohol film is 0.1% to 5%. It is understandable that if the water content is too low, it will easily lead to high crystallinity, small crystal specific surface area, and difficulty in dyeing during the polarizing film processing; if the water content is too high, it will lead to low crystallinity, and it is easy to increase the amount of polyvinyl alcohol dissolved in the production, resulting in reduced tensile strength of the film and easy film breakage during stretching.

[0086] In the above 8% to 15%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., and the range values ​​between any two of the above point values.

[0087] In the above 0.1% to 5%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.3%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, etc., and the range values ​​between any two of the above point values.

[0088] In the above 15% to 35%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 15%, 17%, 19%, 20%, 22%, 25%, 28%, 30%, 31%, 33%, 34%, 35%, etc., and the range values ​​between any two of the above point values.

[0089] In one embodiment, the water content of the liquid film after tape casting is 18% to 30%.

[0090] In one embodiment, the water content of the polyvinyl alcohol film is 0.5% to 3.5%.

[0091] In one embodiment, the step of heat treating the pre-dried film to obtain the polyvinyl alcohol film includes: heat treating the pre-dried film in sequence using n temperature stages to obtain the polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first increasing and then decreasing, 2≤n≤20.

[0092] It can be understood that the heat treatment of the pre-dried film can be carried out in one or more stages. For example, in one embodiment, a multi-stage heat treatment method is adopted, and the pre-dried film is heat-treated in sequence using n temperature stages to obtain a polyvinyl alcohol film. The temperature distribution of the n temperature stages shows a trend of first rising and then falling, 2≤n≤20. It can be understood that as the casting, drying, and heat treatment steps are gradually carried out, the polyvinyl alcohol casting solution gradually becomes a polyvinyl alcohol film with a low water content. In this process, the drying and crystallization processes of polyvinyl alcohol occur synergistically. Under different water contents and temperature conditions, polyvinyl alcohol tends to form crystals of different sizes and quantities. That is, the use of the above-mentioned heat treatment steps helps to finally obtain a polyvinyl alcohol film with a large crystal specific surface area and a moderate degree of crystallinity.

[0093] In the above 2≤n≤20, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 2, 3, 5, 7, 9, 10, 11, 12, 15, 17, 19, 20, etc., and the range values ​​between any two of the above point values.

[0094] In one embodiment, the step of heat-treating the pre-dried film in sequence at n temperature stages to obtain a polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first rising and then falling, comprises: the pre-dried film is heat-treated for a time t, and under the condition of 0%t to 20%t, the pre-dried film is heat-treated at a first temperature stage, wherein the first temperature stage is 50°C to 80°C; under the condition of 20%t to 40%t, the pre-dried film is heat-treated at a second temperature stage, wherein the second temperature stage is 55°C to 95°C; under the condition of 40%t to 60%t, the pre-dried film is heat-treated at a third temperature stage, wherein the third temperature stage is 70°C to 100°C; under the condition of 60%t to 80%t, the pre-dried film is heat-treated at a fourth temperature stage, wherein the fourth temperature stage is 100°C to 130°C; under the condition of 80%t to 100%t, the pre-dried film is heat-treated at a fifth temperature stage, wherein the fifth temperature stage is 50°C to 98°C; and a polyvinyl alcohol film is obtained.

[0095] In one embodiment, five heat treatment steps can be used. The time for heat treatment of the pre-dried film is t, which refers to the time from the start of heat treatment to the end of heat treatment. The end of heat treatment can be judged based on the water content of the polyvinyl alcohol film being 0.1% to 5%.

[0096] It is understandable that if the temperature in the second to fourth stages is too high, the crystal size will be too large, and if the temperature is too low, the total water content will be too high. In addition, the temperature in the fifth stage is slowly lowered to the ambient temperature to avoid the precipitation of plasticizers (such as glycerin) due to too low a temperature.

[0097] In the above-mentioned 50℃ to 80℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50℃, 55℃, 60℃, 68℃, 70℃, 80℃, etc., and the range values ​​between any two of the above-mentioned point values.

[0098] In the above-mentioned 55°C to 95°C, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 55°C, 60°C, 68°C, 70°C, 80°C, 90°C, 95°C, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0099] In the above-mentioned 70℃ to 100℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 70℃, 80℃, 90℃, 95℃, 100℃, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0100] In the above-mentioned 100℃ to 130℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 100℃, 110℃, 115℃, 120℃, 130℃, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0101] In the above-mentioned 50℃ to 98℃, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 50℃, 60℃, 68℃, 70℃, 80℃, 90℃, 98℃, etc., as well as the range values ​​between any two of the above-mentioned point values.

[0102] In one embodiment, the step of heat-treating the pre-dried film in sequence using n temperature stages includes drying the pre-dried film using a fan; the wind speed of the first temperature stage fan is 5.9 m / s to 12.4 m / s, the wind speed of the second temperature stage fan is 6.6 m / s to 13.1 m / s, the wind speed of the third temperature stage fan is 13.2 m / s to 19.7 m / s, the wind speed of the fourth temperature stage fan is 10.5 m / s to 17.0 m / s, and the wind speed of the fifth temperature stage fan is 11.5 m / s to 18.0 m / s. Furthermore, in another embodiment, the wind speed of the first stage temperature fan is 8.1m / s to 10.3m / s, the wind speed of the second stage temperature fan is 8.8m / s to 10.9m / s, the wind speed of the third stage temperature fan is 15.4m / s to 17.5m / s, the wind speed of the fourth stage temperature fan is 12.7m / s to 14.9m / s, and the wind speed of the fifth stage temperature fan is 13.7m / s to 15.8m / s.

[0103] It is understandable that the wind speed during the heat treatment process will affect the crystal size and quantity of the polyvinyl alcohol film, that is, the use of the above wind speed steps is conducive to finally obtaining a polyvinyl alcohol film with a larger amount, smaller size, and moderate total crystallinity. For example, the wind speed during the heat treatment process can be adjusted by the fan frequency, and calibrated with the wind speed actually tested for the polyvinyl alcohol film. If the wind speed is too fast, the water content will drop too fast and the crystallinity will decrease. If the wind speed is too slow, the water content will drop slowly and the crystallinity will increase.

[0104] It is understandable that the heat treatment effect of the polyvinyl alcohol film can be measured by using the water content of the polyvinyl alcohol film after the final heat treatment as a reference for time.

[0105] In the above-mentioned 5.9m / s to 12.4m / s, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 5.9m / s, 6m / s, 6.1m / s, 6.7m / s, 7m / s, 7.5m / s, 8m / s, 9m / s, 9.6m / s, 10m / s, 11m / s, 12m / s, 12.4m / s, etc., and the range value between any two of the above-mentioned point values.

[0106] In the above-mentioned 6.6m / s to 13.1m / s, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 6.6m / s, 6.7m / s, 7m / s, 7.5m / s, 8m / s, 9m / s, 9.6m / s, 10m / s, 11m / s, 12m / s, 13.1m / s, etc., and the range value between any two of the above-mentioned point values.

[0107] In the above-mentioned 13.2m / s to 19.7m / s, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 13.2m / s, 13.7m / s, 14m / s, 14.5m / s, 15m / s, 16m / s, 16.6m / s, 17m / s, 18m / s, 19m / s, 19.7m / s, etc., and the range value between any two of the above-mentioned point values.

[0108] In the above 10.5m / s to 17.0m / s, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 10.5m / s, 10.7m / s, 11m / s, 12.5m / s, 13m / s, 14m / s, 15.6m / s, 16m / s, 17m / s, etc., and the range value between any two of the above point values.

[0109] In the above-mentioned 11.5m / s to 18.0m / s, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 11.5m / s, 11.7m / s, 12m / s, 12.5m / s, 13m / s, 14m / s, 15.6m / s, 16m / s, 17m / s, 18.0m / s, etc., and the range value between any two of the above-mentioned point values.

[0110] In one embodiment, the degree of polymerization of polyvinyl alcohol is 1200 to 4000. It is understandable that if the degree of polymerization is too low, the stability of the molecular chain entanglement network of the prepared polyvinyl alcohol polarizing film will be worse, the polyiodide ion will be more unstable, and it will be more unfavorable to improve the durability; if the degree of polymerization is too high, it will cause excessive tensile tension in the processing of the polarizing film, excessive internal stress of the polarizing film product, and serious shrinkage problems will occur under high temperature and high humidity.

[0111] In one embodiment, the alcoholysis degree of polyvinyl alcohol is 98% to 99.9%. It is understandable that, if the alcoholysis degree is too low, the hydrogen bond network stability of the prepared polyvinyl alcohol polarizing film will be worse, the polyiodide ions will be less stable, and the film durability will be worse under high temperature and high humidity.

[0112] In one embodiment, the polyvinyl alcohol includes at least one of a polyvinyl alcohol homopolymer and a polyvinyl alcohol copolymer, and the comonomer used to prepare the polyvinyl alcohol copolymer includes at least one of olefins, acrylates, methacrylates, methacrylamide derivatives, vinyl esters, and halogenated vinyls, and the mass percentage of the comonomer to the mass percentage of the vinyl alcohol monomer is 0% to 10%. It is understood that if the mass percentage of the comonomer to the mass percentage of the vinyl alcohol monomer is too high, the solubility of the polyvinyl alcohol and the optical properties of the polyvinyl alcohol film will be affected.

[0113] The test steps of the degree of polymerization of polyvinyl alcohol are as follows: the polyvinyl alcohol raw material is dissolved to prepare a solution with a mass concentration of about 0.5%. The accurate mass concentration is measured by dry weighing method, recorded as c. The solution concentration is measured using an Ostwald viscometer fixed in a constant temperature bath. The time required for the sample and deionized water to flow through the upper and lower scale lines of the viscometer is measured, recorded as S0 and S respectively, in seconds. The degree of polymerization PA is calculated according to the following formula:

[0114] ).

[0115] The degree of alcoholysis usually refers to the percentage of hydroxyl groups in the product after the alcoholysis reaction.

[0116] The test steps of alcoholysis degree are as follows: Weigh 1~2mg of polyvinyl alcohol (PVA) raw material, add 0.5mL of fully deuterated dimethyl sulfoxide (DMSO-D6) to dissolve, and measure 1H NMR. In the nuclear magnetic hydrogen spectrum, first integrate the peak at 1.0~1.8ppm (-CH2 in PVA), normalize the integrated area of ​​the peak to "200", and then integrate the multiple peaks at 1.85~2.06ppm (-CH3 peaks of the unalcoholized part of PVA), the integrated area is a, and the calculation formula of alcoholysis degree is: .

[0117] In the above 1200 to 4000, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 1200, 1500, 1800, 2000, 2500, 3000, 3500, 4000, etc., as well as the range values ​​between any two of the above point values.

[0118] In the above 98% to 99.9%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 98%, 98.5%, 99.0%, 99.5%, 99.9%, etc., and the range values ​​between any two of the above point values.

[0119] In the above 0% to 10%, the values ​​include the minimum and maximum values ​​of the range, and every value between the minimum and maximum values. Specific examples include but are not limited to the point values ​​in the embodiments and 0.1%, 0.5%, 1%, 2%, 5%, 6%, 7%, 9%, 10%, etc., and the range values ​​between any two of the above point values.

[0120] In one embodiment, the degree of polymerization of the polyvinyl alcohol is 2000-3500.

[0121] In one embodiment, the alcoholysis degree of the polyvinyl alcohol is 99% to 99.9%.

[0122] In one embodiment, the olefins include non-polar α-olefin comonomers, and the mass of the non-polar α-olefin comonomers accounts for 0% to 5% of the mass of the vinyl alcohol monomer. It is understandable that non-polar α-olefin comonomers, such as ethylene, butene, etc., can be added to polyvinyl alcohol during polymerization to adjust the crystallization performance. If the addition amount is too high, it is easy to form non-polar segments composed of continuous non-polar repeating units on the molecular chain, which leads to phase separation and affects the uniformity of the optical film; if the addition amount is too low, there is no crystallization regulation effect.

[0123] In one embodiment, the mass percentage of the non-polar α-olefin comonomer to the mass percentage of the vinyl alcohol monomer is 0% to 3%.

[0124] In one embodiment, the additives include plasticizers, surfactants, antioxidants and ultraviolet absorbers to improve the properties of the polyvinyl alcohol film.

[0125] In one embodiment, the solvent includes water or dimethyl sulfoxide.

[0126] In one embodiment, the mass fraction of the solute in the casting solution is 20% to 40%.

[0127] In one embodiment, the dissolution temperature of the membrane stock solution is 130° C. to 170° C., and the dissolution time of the membrane casting stock solution is 2 h to 10 h.

[0128] In one embodiment, the plasticizer includes at least one of glycerol, diglycerol, polyglycerol, ethylene glycol and propylene glycol.

[0129] In one embodiment, the surfactant includes a nonionic surfactant and an anionic surfactant. The anionic surfactant includes potassium laurate, dodecylbenzene sulfonate, etc.; the nonionic surfactant includes polyoxyethylene lauryl ester, polyoxyethylene lauryl amino ester, polyoxyethylene lauric acid amide, etc.

[0130] In one embodiment, the mass percentage of the plasticizer to the mass percentage of the polyvinyl alcohol is 8% to 15%, and the mass percentage of the surfactant to the mass percentage of the polyvinyl alcohol is 1.0‰ to 5.0‰. Too much plasticizer and surfactant will cause the plasticizer and surfactant to precipitate, resulting in deterioration of the optical properties of the polyvinyl alcohol film.

[0131] In one embodiment, the mass fraction of the solute in the casting solution is 25% to 35%.

[0132] In one embodiment, the dissolution temperature of the casting solution is 145° C. to 160° C., and the dissolution time is 4 h to 7 h.

[0133] In one embodiment, during the pre-drying process of the film, m drying rollers are sequentially used to dry the film formed by tape casting, and the temperature of the m drying rollers shows a trend of gradually decreasing, 8≤m≤20, and the temperature of the drying rollers is 30° C. to 90° C. The above drying mode can ensure the uniformity of the film during the drying process and reduce the damage to the film caused by excessive temperature.

[0134] In one embodiment, the pre-dried film is heat treated in an oven such that the heat treatment step is performed continuously.

[0135] In one embodiment, after the casting solution is degassed, cast and pre-dried, in the step of obtaining a pre-dried film, the casting solution is degassed by an extruder, and the head pressure of the extruder is 1.0 MPa to 3.0 MPa. It is understood that the casting solution is degassed by an extruder, and the head pressure is within the above range. If the pressure is too low, the degassed effect is poor, and if the pressure is too high, the equipment load is too large.

[0136] In one embodiment, in the step of dissolving polyvinyl alcohol and additives in a solvent to obtain a membrane casting solution, a disc filter is used to filter the membrane casting solution. The pore size of the disc filter is 1um to 20um. The membrane casting solution is filtered through the disc filter to remove impurities, gel, etc. The pore size of the filter is 1um to 20um, for example, 2um to 10um. If the pore size of the filter is too large, the impurity gel cannot be removed. If the pore size is too small, the pressure drop is too large, and the power load of the equipment increases.

[0137] In the present application, through the above-mentioned preparation method, each step is coordinated, such as adjusting the temperature and air flow rate during the heat treatment process, so that the external field parameters such as the temperature and wind speed curve during the processing are matched with the decreasing curve of the water content of the film and the crystallization process occurring inside, thereby obtaining a polyvinyl alcohol film with a polymer structure having a large number, a small size and a moderate total crystallinity.

[0138] This application starts from the microstructure of polyvinyl alcohol, combines polymer crystallization theory with the production process of polyvinyl alcohol film, and is conducive to the preparation of a more stable iodine-polyvinyl alcohol complex. This application starts from the raw materials for preparing polyvinyl alcohol polarizing film, designs the crystal structure required by the raw materials, and is used to obtain a more stable iodine-polyvinyl alcohol complex, which has the characteristics of more significant effects. And it has the advantage of having little impact on the process, equipment, and product performance of downstream polarizing film processing.

[0139] The present application controls the crystal structure of the polyvinyl alcohol film by controlling the temperature and wind speed of each section of the heat treatment process, and can accurately and efficiently control the stability of the polyvinyl alcohol film crystal network, the crystal specific surface area and the crystal content, thereby helping to improve the durability of the polarizing film. In addition, the regulation based on the heat treatment process is simple and effective, does not require large-scale equipment changes, and has good adaptability.

[0140] Example

[0141] Example 1

[0142] Preparation of polyvinyl alcohol film: 32kg of polyvinyl alcohol polymer (PVA) (polymerization degree 2400, alcoholysis degree 99.8%), sodium dodecylbenzene sulfonate, glycerol and antioxidant mixture (wherein the plasticizer content accounts for 15% of the PVA mass, and the surfactant content accounts for 5‰ of the PVA content) and 68L of deionized water are put into the reactor, stirred at 150℃ and 0.4MPa for 6h to dissolve, and a PVA casting solution with a solute content of 35% is obtained. The formed casting solution is degassed by an extruder with a die pressure of 0.5MPa, and is filtered through a 6um filter and extruded from the die. After drying by a casting roller, the water content is reduced to 35%, and then it enters the drying roller for pre-drying, and the water content is reduced to 15%. Then it enters the oven for heat treatment, and finally rolled up to obtain the PVA film. The heat treatment section is designed to be divided into five sections, each with the same length. The temperatures are 70°C, 72°C, 86°C, 118.5°C, and 65°C respectively. By controlling the fan frequency, the wind speeds blowing onto the membrane surface are 9.2m / s, 9.8m / s, 16.4m / s, 13.8m / s, and 14.8m / s respectively.

[0143] Preparation of polyvinyl alcohol polarizing film: Sample preparation was performed using homemade solutions and stretching devices. The polyvinyl alcohol film prepared above was first treated in a constant temperature and humidity chamber for 24 hours at a temperature of 23±1°C and a humidity of 55±5%Rh. The balanced polyvinyl alcohol film was cut into 60*40mm pieces along the stretching direction for later use. The process parameters for dyeing and stretching experiments are shown in Table 1 below. Dyeing solution and cleaning solution were prepared as needed, and 150mL was used for each polyvinyl alcohol film, which was used once and discarded after use. The stretching liquid was prepared according to the actual volume of the solution stretching device. The stretching of the specified stretching ratio was completed evenly within the specified time, and then the length was fixed and taken out. The remaining steps were to soak in a liquid container of the corresponding temperature for a specified time. After completion, it was dried in a 65°C blast oven for 5 minutes. The swelling step was performed in deionized water.

[0144] Table 1. Dyeing and stretching test process parameters

[0145]

[0146] Durability test method

[0147] The optical performance of the polyvinyl alcohol polarizing film is tested. A spectrophotometer with polarization function is used to measure the transmittance spectrum with the polarization direction perpendicular to the film stretching direction, and the wavelength sampling interval is less than or equal to 5nm. The five transmittance values ​​at 600, 605, 610, 615, and 620nm are averaged to avoid the influence of film interference on the transmittance measurement during the test. The transmittance is converted into absorbance. According to Lambert-Beer's law, the absorbance value is proportional to the content of polyiodide ions oriented along the stretching direction. The ratio of the above absorbance measurement value of the original sample to the absorbance value measured after heat aging treatment at 95 degrees Celsius * 5h in a blast drying oven is calculated as an indicator of the durability of the sample.

[0148] Water absorption rate curve experiment

[0149] Cut a 50*50mm size polyvinyl alcohol film sample, swell it in 300mL of 30℃ water for T minutes, take it out after the specified time, scrape off the surface water droplets and weigh it, which is calculated as m1. Dry it in a 120℃ blast oven for 2h, take it out and weigh it as m2, T can be in the range of 0.1min to 30min. Use a separate piece of film for each water absorption test and it cannot be reused. Water absorption = (m1- m2) / m2*100%.

[0150] In this application, the water absorption at two time points of 1min and 15min is mainly used, and the value of the water absorption at 1min and the water absorption at 15min is calculated. This value can represent the ratio of the fast swelling part to the slow swelling part in the polyvinyl alcohol film, which corresponds to the swelling of the amorphous region and the dissolution process of the crystal surface defect structure. The lower the value, the greater the proportion of the crystal surface defect structure. When the polyvinyl alcohol film swells in water, the amorphous region absorbs water and expands first. For 30um to 60um films, this process mainly occurs within one minute. Subsequently, water molecules gradually destroy the hydrogen bonds of the crystal surface defect structure, destroying the less stable crystal surface defect structure until a stable crystal is encountered. This process is slow, and it is currently believed that it can be basically completed within 15min at 30°C. The less stable crystal surface defect structure is equivalent to being wrapped outside the stable crystal. Therefore, the more unstable crystal surface defect structures account for, the larger the specific surface area of ​​the crystal particles and the smaller the size of the single crystal.

[0151] Example 2

[0152] This example was prepared by the same method and conditions as Example 1, except that:

[0153] In the second and third stages, the wind speeds blowing onto the membrane surface were 10.5m / s and 17.3m / s respectively by controlling the fan frequency.

[0154] Example 3

[0155] This example was prepared by the same method and conditions as Example 1, except that:

[0156] The temperatures of the second and third heat treatment stages were 84°C and 98°C, respectively. The wind speeds blowing onto the membrane surface in the second and third stages were 10.1 m / s and 16.8 m / s, respectively, by controlling the fan frequency.

[0157] Comparative Example 1

[0158] This example was prepared by the same method and conditions as Example 1, except that:

[0159] The temperature of the fourth section of the heat treatment stage was 132°C, and the wind speeds blowing onto the membrane surface in the second and third sections were 10.5 m / s and 17.3 m / s respectively by controlling the fan frequency.

[0160] Comparative Example 2

[0161] This example was prepared by the same method and conditions as Example 1, except that:

[0162] The temperatures of the second, third and fourth heat treatment sections were 84°C, 98°C and 123.5°C respectively. The wind speeds blowing to the membrane surface in the second and third sections were 6.5m / s and 12.5m / s respectively by controlling the fan frequency.

[0163] Comparative Example 3

[0164] This example was prepared by the same method and conditions as Example 1, except that:

[0165] The temperature of the fourth section of the heat treatment stage was 132°C, and the wind speeds blowing onto the membrane surface in the second and third sections were 6.5 m / s and 12.5 m / s respectively by controlling the fan frequency.

[0166] Comparative Example 4

[0167] This example was prepared by the same method and conditions as Example 1, except that:

[0168] The temperature of the fourth section of the heat treatment stage was 123.5°C, and the wind speeds blowing onto the membrane surface in the second and third sections were 10.5m / s and 17.3m / s respectively by controlling the fan frequency.

[0169] Comparative Example 5

[0170] This example was prepared by the same method and conditions as Example 1, except that:

[0171] The temperatures of the second, third and fourth heat treatment sections were 84°C, 98°C and 123.5°C respectively. The wind speeds blowing to the membrane surface in the second and third zones were 10.5m / s and 17.3m / s respectively by controlling the fan frequency.

[0172] Comparative Example 6

[0173] This example was prepared by the same method and conditions as Example 1, except that:

[0174] The temperature of the fourth section of the heat treatment stage was 123.5°C, and the wind speeds blowing onto the membrane surface in the second and third sections were 9.8 m / s and 16.4 m / s respectively by controlling the fan frequency.

[0175] Table 2. Experimental list of process parameters and test results of samples of different embodiments and comparative examples

[0176]

[0177] In the present application, x / (x+y) is 0.82 to 0.93, the softening point of the polyvinyl alcohol film is 65°C to 75°C, and the swelling degree of the polyvinyl alcohol film is 180% to 220%. Under the above conditions, the durability of the polyvinyl alcohol polarizing film prepared using the polyvinyl alcohol film is improved.

[0178] It can be seen from Table 2 that, under the above conditions of the present application, the 610nm absorbance retention rate of the polarizing film is better, indicating that the durability of the polarizing film is improved.

[0179] Moreover, after the casting solution is subjected to tape casting, drying, and heat treatment in Examples 1, 2, and 3, the obtained polyvinyl alcohol film satisfies the preparation process conditions of the present application and the condition that x / (x+y) in the polyvinyl alcohol film is 0.82 to 0.93, and the polarizing film prepared by dyeing and stretching has a relatively good durability index. In Comparative Examples 1, 2, and 3, the processing parameters exceed the ranges described above, and a film with the expected crystal structure cannot be obtained, and its durability is poor.

[0180] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A polyvinyl alcohol film, characterized in that The saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x, and the increased water absorption of the polyvinyl alcohol film due to the destruction of the crystal surface defect structure is y, and x / (x+y) is 0.82 to 0.93; The testing step of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film comprises: soaking at least one portion of the polyvinyl alcohol film in deionized water at a preset temperature for a preset time t1, taking out the polyvinyl alcohol film after the amorphous structure in the polyvinyl alcohol film has finished absorbing water, scraping off the water droplets on the surface of the polyvinyl alcohol film and weighing it, which is calculated as m x1 , the polyvinyl alcohol film is dried and weighed, which is m x2 The saturated water absorption of the amorphous structure in the polyvinyl alcohol film is x = (m x1 -m x2 ) / m x2 *100%; The testing step of the sum of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film and the water absorption increased due to the destruction of the crystal surface defect structure in the polyvinyl alcohol film comprises: soaking at least one portion of the polyvinyl alcohol film in deionized water at a preset temperature for a preset time t2 to destroy the crystal surface defect structure in the polyvinyl alcohol film, and after the destroyed crystal surface defect structure finishes absorbing water, taking out the polyvinyl alcohol film, scraping off the water droplets on the surface of the polyvinyl alcohol film and weighing it, which is calculated as m x3 , the polyvinyl alcohol film is dried and weighed, which is m x4 The sum of the saturated water absorption of the amorphous structure in the polyvinyl alcohol film and the water absorption increased by the crystal surface defect structure in the polyvinyl alcohol film is x+y=(m x3 -m x4 ) / m x4 *100%; The softening point of the polyvinyl alcohol film is 65° C. to 75° C., and the swelling degree of the polyvinyl alcohol film is 180% to 220%; The polyvinyl alcohol film has a crystallinity of 35% to 45%, and a melting point of 210° C. to 230° C.

2. The polyvinyl alcohol film according to claim 1, characterized in that The x / (x+y) is 0.84 to 0.

89.

3. The polyvinyl alcohol film according to claim 1, characterized in that The preset temperature is 30° C., the t1 is 1 min, and the t2 is 15 min.

4. A method for preparing a polyvinyl alcohol film according to any one of claims 1 to 3, characterized in that: include: Dissolving polyvinyl alcohol and additives in a solvent to obtain a film casting stock solution; The film casting solution is subjected to degassing, tape casting and pre-drying to obtain a pre-dried film; The pre-dried film is heat-treated to obtain a polyvinyl alcohol film.

5. The method for preparing a polyvinyl alcohol film according to claim 4, characterized in that: In the step of obtaining a pre-dried film after degassing, casting and pre-drying the casting solution, the water content of the liquid film after casting is 15% to 35%; And / or, in the step of obtaining a pre-dried film after degassing, casting and pre-drying the film casting solution, the water content of the pre-dried film is 8% to 15%; And / or, in the step of heat-treating the pre-dried film to obtain a polyvinyl alcohol film, the water content of the polyvinyl alcohol film is 0.1% to 5%.

6. The method for preparing a polyvinyl alcohol film according to claim 4, characterized in that: The water content of the liquid film after tape casting is 18% to 30%; And / or, the water content of the polyvinyl alcohol film is 0.5% to 3.5%.

7. The method for preparing a polyvinyl alcohol film according to any one of claims 4 to 6, characterized in that: The step of heat-treating the pre-dried film to obtain a polyvinyl alcohol film includes: heat-treating the pre-dried film in sequence using n temperature stages to obtain a polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first increasing and then decreasing, and 2≤n≤20.

8. The method for preparing a polyvinyl alcohol film according to claim 7, characterized in that: The step of heat-treating the pre-dried film in sequence using n temperature stages to obtain a polyvinyl alcohol film, wherein the temperature distribution of the n temperature stages shows a trend of first increasing and then decreasing, comprises: The pre-dried film is heat-treated for a time of t, and the pre-dried film is heat-treated at a first temperature range of 50° C. to 80° C. under a condition of 0% t to 20% t; Under the condition of 20%t to 40%t, the pre-dried film is heat-treated with a second temperature, wherein the second temperature is 55°C to 95°C; Under the condition of 40%t to 60%t, the pre-dried film is heat-treated at a third temperature, wherein the third temperature is 70°C to 100°C; Under the condition of 60%t to 80%t, the pre-dried film is heat-treated at a fourth temperature, wherein the fourth temperature is 100°C to 130°C; The pre-dried film is heat treated at a fifth temperature under a condition of 80%t to 100%t, wherein the fifth temperature is 50°C to 98°C; and a polyvinyl alcohol film is obtained.

9. The method for preparing a polyvinyl alcohol film according to claim 8, characterized in that: The step of sequentially heat treating the pre-dried film using n temperature stages includes drying the pre-dried film using a fan; The wind speed of the fan in the first temperature section is 5.9m / s to 12.4m / s, the wind speed of the fan in the second temperature section is 6.6m / s to 13.1m / s, the wind speed of the fan in the third temperature section is 13.2m / s to 19.7m / s, the wind speed of the fan in the fourth temperature section is 10.5m / s to 17.0m / s, and the wind speed of the fan in the fifth temperature section is 11.5m / s to 18.0m / s.

10. The method for preparing a polyvinyl alcohol film according to claim 9, characterized in that: The wind speed of the fan in the first temperature section is 8.1m / s to 10.3m / s, the wind speed of the fan in the second temperature section is 8.8m / s to 10.9m / s, the wind speed of the fan in the third temperature section is 15.4m / s to 17.5m / s, the wind speed of the fan in the fourth temperature section is 12.7m / s to 14.9m / s, and the wind speed of the fan in the fifth temperature section is 13.7m / s to 15.8m / s.

Citation Information

Patent Citations

  • Polyvinyl alcohol-type polymer film and polarizing film

    CN104204046A

  • Polyvinyl alcohol film with good durability and preparation method thereof

    CN109438734A

Cited By

  • Polyvinyl alcohol film and preparation method therefor

    EP4782500A1